Husband-wife team offer musical mix (Raton, NM Raton Range, 1997)
Article is to promote Kim and Reggie Harris who are singers, composers and recording artist that are going to be performing at the Shuler Theater.
Newspaper article + Photograph of Kim and Reggie Harris
Master list item #: 81
File location is in the Raton file Cabinet
Keywords: Harris, Kim -- Musician; Harris, Reggie -- Musician; New Mexico Arts -- Sponsor; McCune Foundation -- Sponsor; Dairy Queen -- Sponsor; Raton Builders -- Sponsor; Lions Club -- Sponsor; Kiwanis Club -- Sponser; Art Promotion; Live Performance; Musical Performance; Shuler Theater; Raton, New Mexico